Office 2010 web apps for dummies - Weverka, Peter (For dummies, 2011)
Office Web Apps complement Office, making it easy to access and edit files from anywhere. It also simplifies collaboration with those who don?t have Microsoft Office on their computers. This helpful book shows you the optimum ways you can use Office Web Apps to save time and streamline your work. Veteran For Dummies author Peter Weverka begins with an introduction to Office Web Apps and then goes on to clearly explain how Office Web Apps provide you with easier, faster, more flexible ways to get things done